Ways to increase patient compliance in the drugs preferential provision - E. V. Eliseeva; E. S. Maneeva; A. V. Kropotov (Качественная клиническая практика, 2020)
Compliance of patients in the drugs preferential provision is considered as the most important component of effectiveness and safety pharmacotherapy.Aim. Based on the study of patient compliance in the drugs preferential provision program to develop recommendations and proposals to improve adherence to treatment.Materials and methods. A sociological survey was conducted at 115 patients suffering from chronic diseases in four polyclinics in Vladivostok in 2019. All patients were treated under the «Program of Providing Certain Categories of Citizens with Necessary Drugs». The study used descriptive statistics methods using the Microsoft Office program.Results. The highest level of adherence was noted in the indicators «compliance with the recommendations of the attending physician for taking medicines» — 78.3 % and «absence of a pass in taking medicines» — 76.5 %. The greatest compliance to drugs treatment (< 50 %) on the majority of indicators of questioning is registered at patients with diagnoses: «diabetes mellitus», «bronchial asthma» and «malignant neoplasms», and also at co-morbid patients. The lowest adherence to pharmacotherapy (> 50 %) was in groups of patients with hypertension and chronic renal failure. Compliance in the field of non-drugs treatment is not sufficient.Conclusion. The sociological survey showed that adherence to medication and non-medication treatment is insufficient. To improve the compliance it is recommended the introduction of programs of patient education with use of modern interactive educational technologies.